BAKER, Paul; BALIRANO, Giuseppe (ed.). Queering Masculinities in Language and Culture. Series: Studies in Language, Gender and Sexuality. Londres: Palgrave Macmillan, 2018. 299p. ISBN: 978-1-349-95327-1 (eBook).: Resenha - Souza, Glauco' (Cadernos de Linguagem e Sociedade, 2020)
Resenha